Implementasi Algoritma Support Vector Machine (SVM) Untuk Penentuan Seleksi Atlet Pencak Silat - Eni Hartika Harahap; Lailil Muflikhah; Bayu Rahayudi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Pencak Silat is a traditional martial art originating from Indonesia. Along with an evolution of the time pencak silat is not only used to protect and defend themselves from opponents, but also show in a contest. Determination of the final result in selection that still counts the manual becomes main obstacle of the jury when one of the parties can't accept defeat while competing. To overcome these problems required a classification system that is able to classify enrolment acceptance of the pencak silat athletes had eligible pass the support vector machine (SVM) method by the SVM classifying the data into two classes. The data used in this research is 110 whitch is divided into training data and test data with 2 classes of acceptance of selection is pass and not pass. The best accuracy result in this research based on experiment ratio of data 70% : 30%, using kernel Polynomial Degree d = 2 and parameter value Î» (lamda) = 0,1, Î³ (gamma) = 0,0001, Îµ (Epsilon) = 0.000001, C (Complexity) = 0.00001 and Itermax = 250. Kernel use in this research value of Polynomial Degree 2. The average result of accuracy using SVM method in the classification enrolment of the Pencak Silat athletes is 69,09 %.